The Impact of Industrial IoT (IIoT) and Edge Computing Adoption on the Operational Performance of Manufacturing Companies in Central Java - Susatyo Handoko; Karnoto Karnoto (Westscience Press, 2025)
This study investigates the impact of Industrial Internet of Things (IIoT) and Edge Computing implementation on the operational performance of manufacturing companies in Central Java. A quantitative research approach was employed, involving 150 respondents selected using purposive sampling. Data were collected through a structured Likert-scale questionnaire and analyzed using SPSS version 25, including descriptive statistics, correlation, and multiple linear regression. The results indicate that both IIoT and Edge Computing have a significant positive effect on operational performance, explaining 54% of the variance. Specifically, IIoT enhances real-time monitoring, predictive maintenance, and overall production efficiency, while Edge Computing reduces latency and accelerates data-driven decision-making. The findings provide practical insights for manufacturing managers seeking to optimize operations through advanced digital technologies.